PEMASARAN RELUNG (NICHE MARKETING) SEBAGAI STRATEGI MEMBIDIK PASAR YANG LEBIH KECIL - James Rianto Situmorang (Jurnal Administrasi Bisnis, 2022)
Niche marketing has not been the first choice for companies in carrying out their marketing strategy. Most companies prefer to fight in the mainstream market even though the opportunities are not very good. Niche marketing has long been implemented by several companies and achieved success, for example, the Apple company when pioneering the PC business. Nowadays, niche marketing is not only done by small companies but also by large companies. Companies aiming at smaller markets are expected to provide a greater chance of success because the level of competition is not as tight as the mainstream market. A smaller niche market makes the company more focus on that specific market.